2006
DOI: 10.3354/meps328295
|View full text |Cite
|
Sign up to set email alerts
|

Feeding mechanism of the polychaete Sabellaria alveolata revisited: comment on Dubois et al. (2005)

Abstract: Recently, Dubois et al. (2005; Mar Ecol Prog Ser 301:159-171) described the feeding mechanisms of the sabellariid polychaete Sabellaria alveolata and concluded that it is a ciliary suspension feeder that uses alternately a downstream-and an upstream-collecting system. We reinvestigated both the ciliated epithelia (scanning electron microscopy and transmission electron microscopy) and the function (video microscopy) of the tentacle crown of S. alveolata. We found that the tentacles of intact and undisturbed S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 21 publications
3
32
2
Order By: Relevance
“…The fluid mechanical significance of the ciliary spikes remains unknown. However, the observations made by Riisgård & Nielsen (2006) suggest that mucus is involved in both the capture and transport of food particles in S. alveolata, possibly in a similar way as found in spionid polychaetes (Shimeta et al 2004). …”
Section: Ciliary-spike Suspension Feedingmentioning
confidence: 94%
See 1 more Smart Citation
“…The fluid mechanical significance of the ciliary spikes remains unknown. However, the observations made by Riisgård & Nielsen (2006) suggest that mucus is involved in both the capture and transport of food particles in S. alveolata, possibly in a similar way as found in spionid polychaetes (Shimeta et al 2004). …”
Section: Ciliary-spike Suspension Feedingmentioning
confidence: 94%
“…However, Riisgård & Nielsen (2006) re-investigated both the ciliated epithelia and the function of the tentacle crown of S. alveolata. It was found that the tentacles of intact and undisturbed S. alveolata have a large number of ciliary spikes (compound cilia), which are usually kept stiff, but which may beat parallel to the length of the tentacle, each flanked by an actively beating cirrus.…”
Section: Ciliary-spike Suspension Feedingmentioning
confidence: 99%
“…Sensory organs, such as the apical organ, palps, tentacles, statocysts, eyespots and nuchal organs have been documented in sabellariid larvae and adult stages (Orrhage 1978;Kirtley 1994). The suggested functions of those organs with external ciliation include chemoreception, mechanoreception, and feeding (Eckelbarger 1977(Eckelbarger , 1978Pennington & Chia 1984;Smith & Chia 1985;Dubois et al 2005;Riisgård & Nielsen 2006). In some species, the median organs can bear tufts of cilia (e.g., Lygdamis nasutus n.…”
Section: Discussionmentioning
confidence: 99%
“…As admitted by the authors, the scanning electron micrograph (SEM) photographs provided by Riisgård & Nielsen (2006) display a very obvious fixation artefact, due to hypotonic fixation (Beninger et al 1995), which could have been avoided by measuring the osmolarity of their specimens' habitat and adjusting their solution accordingly. Hypotonic fixation is responsible for paddle cilia formation and other terminal irregularities, as well as partial disorganization of ciliary structures, leading to ambiguous functional interpretation.…”
Section: Ciliation Of Tentacular Filamentsmentioning
confidence: 99%
“…Hypotonic fixation is responsible for paddle cilia formation and other terminal irregularities, as well as partial disorganization of ciliary structures, leading to ambiguous functional interpretation. A slightly hyperosmotic solution is necessary to fix polychaete ciliated feeding organs while ABSTRACT: The high-speed videos provided by Riisgård & Nielsen (2006;this volume) allow new insights into Sabellaria alveolata feeding processes, but the interpretation of these video observations is compromised both by artifacts of sample preparation and premature dismissal of our findings in Dubois et al (2005;Mar Ecol Prog Ser 301:159-171). S. alveolata appears clearly to be an active suspension-feeder, while not using grouped lateral cilia to catch particles directly from the water column, but by using both the grouped lateral cilia and grouped frontal cilia to modify current patterns around tentacular filaments to entrain suspended particles.…”
Section: Ciliation Of Tentacular Filamentsmentioning
confidence: 99%